Sitotoksisitas Ekstrak Daun Kopi Robusta (Coffea canephora) terhadap Sel Vero - Mastuti Widianingsih; M. Rofi Putra Bani; Putri Amalia (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Robusta coffee leaves (Coffea canephora) contain various bioactive compounds that may serve as natural antioxidants and potential phytopharmaceutical agents. The objective of this research to evaluate the antioxidant activity and cytotoxicity of the ethanol extract of robusta coffee leaves and to determine the relationship between antioxidant activity and cell viability. Antioxidant activity was assessed using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, while cytotoxicity was evaluated on Vero cells using the MTT assay over a concentration range of 31.25-500 µg/mL. Vitamin C and doxorubicin were used as positive controls. The ethanol extract exhibited very strong antioxidant activity with an IC50 value of 22.456 µg/mL, while vitamin C showed an IC50 value of 4.217 µg/mL. Cytotoxicity testing demonstrated low toxicity toward Vero cells, with an IC50 value of 1512.857 µg/mL, whereas doxorubicin exhibited an IC50 value of 60.052 µg/mL. Pearson correlation analysis revealed a strong negative correlation between antioxidant activity and Vero cell viability (r = −0.93, p = 0.024). Despite this correlation, cell viability remained above 100% at all tested concentrations, indicating the absence of cytotoxic effects on normal mammalian cells. These findings suggest that the ethanol extract of robusta coffee leaves possesses potent antioxidant activity while maintaining a favorable safety profile, supporting its potential to be futher development as a source of natural antioxidants and phytopharmaceutical candidate.